Factors Affecting Delay in Reporting Village Government Financial Accountability in Delima Subdistrict, Pidie Regency - Hamdiah, Cut; Maisur, Maisur (Budapest International Research and Critics University, 2021)
The purpose of this study is to analyze the factors that affect the delay in reporting village government financial accountability in the Delima District, Pidie Regency. The sample in this study were 44 financial groups. In determining the sample using saturated sampling andfield research method. While the analysis toolused is multiple linear regression. From the results of the analysis obtainedThe factors that cause the dominant delay are the HR factor on the educational background indicator, information technology on the application update indicator, supporting facilities on the internet indicator, the internal control system on the dual position indicator, and the rule of law on the indicator of minimal understanding of legislation. The implication of this research for the working unit is that it can improve the quality of timely submission of financial reports.